The relationship between the perceived care and rehabilitation and the anxiety level of the hospitalized patients - Yildirim, Hilal (Annals of Medical Research, 2021)
Aim: The objective of this study is to determine the relationship between “perceived care and rehabilitation”, and the “anxiety level” of hospitalized patients. This research also aims to determine the factors affecting this relationship.Materials and Methods: This descriptive and cross-sectional study was conducted with 205 patients who diagnosed with any disease in Malatya Training and Research Hospital Internal Medicine Department. The participants were selected and admitted using a non-probability sampling method among the patients. Data were collected using patient introduction forms, perceived care and rehabilitation scale, and state-trait anxiety inventory.Results: We identified a negative relationship between the anxiety of the patients and their perceived care and rehabilitation. The anxiety levels of the patients were slightly above the medium level. Some features such as the education level, income, and inpatient duration of the patients had an impact on the perceived care and rehabilitation scales. The research also revealed that marital statuses, partnership, worries about the risks of the disease are some of the factors affecting the perceived care and rehabilitation, and the anxiety level of the patients. Conclusion: The research analysis revealed that the improvement in the perception of care and rehabilitation decreases the level of anxiety. Customizing patient care according to the personal experiences of each patient and managing the health care process in this context may decrease the anxiety level and thus may improve the health of the patient.
Keywords: Anxiety; hospitalization; inpatient care; patient; perceived care and rehabilitation